고등학생의 성폭력 경험, 성폭력 인식 및 성역할 태도 - 차영주(Young Joo Cha); 최연희(Yeon Hee Choi) (지역사회간호학회지, 2008)
Purpose: This study was conducted to identify relations among experience of sexual assaults, recognition of sexual assaults and sex role attitude in urban and rural high school students. Method: The subjects were a 575 volunteer students sampled in Daegu City and Gyungbuk. Data were collected from March 19th to 31st, 2007 using structured questionnaires. Collected data were analyzed with the SPSS program using descriptive statistics. Chi-square test, t-test, Pearson's correlation coefficient, and multiple regression. Results: The mean score of the rural students was significantly higher than that of the urban students in experience of sexual assaults. The mean score of the urban students was significantly higher than that of the rural students in sex role attitude. Gender, experience of sexual education and recognition of sexual assaults accounted for 29.8% of the variance of sex role attitude in the urban students. Conclusion: It is necessary to develop discriminative sexual education programs by regional group in order to prevent sexual assaults among adolescents.